1990
DOI: 10.1105/tpc.2.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nuclear factors with upstream sequences of a lipid body membrane protein gene from carrot.

Abstract: To study the regulation of gene expression during embryo development, we isolated a gene, DC 59, expressed in embryos but not in mature carrot plants. Sequence and S I analysis showed that the gene was composed of one exon encoding a polypeptide of 19 kilodaltons and was highly homologous to the lipid body membrane protein gene L3 from maize. The plant hormone abscisic acid regulated the accumulation of DC 59 mRNA. To understand the mechanism of embryo-specific and hormonal regulation of DC 59, 5' DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Recent data indicate that some 5% of oleosin is on endoplasmatic reticulum (ER) segments near oil bodies (Sarmiento et al 1997; Lacey et al 1999). Oleosin genes are expressed during seed development and maturation, and some are induced by abscisic acid (ABA) and desiccation (Hatzopoulos et al 1990; Plant et al 1994). Oleosin‐like mRNA have also been reported in anthers of Arabidopsis and rapeseed (Murphy and Vance 1999).…”
Section: Oleosinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicate that some 5% of oleosin is on endoplasmatic reticulum (ER) segments near oil bodies (Sarmiento et al 1997; Lacey et al 1999). Oleosin genes are expressed during seed development and maturation, and some are induced by abscisic acid (ABA) and desiccation (Hatzopoulos et al 1990; Plant et al 1994). Oleosin‐like mRNA have also been reported in anthers of Arabidopsis and rapeseed (Murphy and Vance 1999).…”
Section: Oleosinmentioning
confidence: 99%
“…AtClo1–4 expression is not responsive to ABA or osmotic stress in vegetative tissues, as was the case for rice OsClo . Carrot oleosin is only responsive to ABA in embryonic tissue, and not in adult tissue (Hatzopoulos et al 1990). Whether AtClo1–4 expression in embryos is responsive to ABA remains to be determined.…”
Section: Caleosin Expression Patternsmentioning
confidence: 99%
“…The former MITE could be attributed to the DcSto group. Also, we identified a DcSto element inserted in the region upstream carrot lipid body membrane protein gene (Hatzopoulos et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…That effect may be one of the reasons for a relatively frequent occurrence of DcSto elements in clusters with other MITEs observed previously and confirmed in the present study. Analysis of the binding capacity of a region upstream a lipid body membrane protein gene from carrot overlapping with the DcSto 9 insertion showed that the region had a potential to form complexes with nuclear extracts from embryos (Hatzopoulos et al 1990). Interestingly, the region identified as responsible for DNA-binding, harbored by DcSto 9, was not present in other DcSto element families.…”
Section: Discussionmentioning
confidence: 99%
“…If a protein or proteins bind to the DNA fragment it will form a complex that will migrate slower in a gel than the DNA fragment alone. The number of identified plant DNA-binding factors is quickly growing (Allen et al, 1989;Hatsopoulos et al, 1990;Lam et al, 1990;Lessard et al, 1991;Meakin and Gatehouse, 1991;Nantel et al, 1991;So and Larkins, 1991;Granell et al, 1992;Ishiguro and Nakamura, 1992;Yanagisawa and Izui, 1992). Factors that bind to AT-rich sequences within a promoter have been identified by gel-shift assays (Cushman and Bohnert, 1992).…”
Section: Complexity Of Transcriptional Regulation In Eucaryotesmentioning
confidence: 99%